PENANAMAN MODAL ASING: KONTROVERSI TERHADAP PERANANNYA DALAM PEMBANGUNAN DI NEGARA SEDANG BERKEMBANG (NSB) - Hertiana Ikasari (MEDIA, 2012)
This paper aims to analyze the pro and cons opinion of foreign investment presence in development of developing countries. In pro opinion of foreign investment (as well as foreign aid), foreign investment is a very positive thing, because it can fill the gap between the supply of savings, foreign exchange reserves, government revenues, and managerial expertise in recipient country with the required level of inventory to be able to achieve growth and development targets. While counter opinion say that foreign investment may lead gap.